Regin Prenter in memoriam - Schjørring, Jens Holger (Grundtvig-studier, 1991)
Obituary of Regin Prenter. Regin Prenter’s name is chiefly connected with his textbook of dogmatics, which is the most important Danish textbook in that field, and which has been translated into several languages. Beyond that, Prenter’s name is associated with his achievement as a Luther scholar.It is, however, worth maintaining that also Grundtvig’s ’ View of the Church’ occupied a prominent position in Prenter’s interpretation of Christianity. Grundtvig’s importance for Prenter did not clash with the fact that in his maturing years as a scholar in the 1930s he was internationally and ecumenically oriented. On the contrary, the inspiration that Prenter received from Karl Barth in Bonn and from Anglican theology (particularly from Michael Ramsey) in Lincoln in 1935 was closely linked to his understanding of Grundtvig.Over a period of 10 years from 1935, Prenter was a clergyman until he became a professor at the newly founded Faculty of Theology of Aarhus University. He abandoned his chair in 1972 when he returned to a clerical office which he held until his retirement.Prenter became increasingly antagonistic towards the leading circles in the Danish national church. In particular, the law about ordination of women roused his indignation; on the whole, his opposition to this law and his own High-Church standpoint in ecclesiastical politics caused him to confront the way of thinking which is traditionally regarded as the church policy inspired by Grundtvig.To Prenter it was entirely unacceptable that the majority in the national church, who claimed to continue the Grundtvig heritage of latitude and spiritual freedom, neglected at the same time what was inextricably associated with Grundtvig as an .old-church. theologian.Prenter’s understanding of the theology of the church service and his understanding of the sacraments may be seen in the light of this conflict, and it should be considered on this background whether Prenter’s theology does not present significant questions for us today.Thus, Prenter’s theology does not deserve to be looked upon as marginal, but should be included in a re-consideration of Danish ecclesiastical and theological tradition as a provocative, but fruitful viewpoint.J.H. Schjørring